Exchange Arrangements and Foreign Exchange Markets : Developments and Issues. (World Economic and Financial Surveys; World Economic and Financial Surveys, 2003)
This paper reviews developments and issues in the exchange arrangements and currency convertibility of IMF members. Against the backdrop of continuing financial globalization and a series of emerging market crises since 1997, there have been important changes in the evolution of exchange rate regimes and the pace of liberalization of current and capital transactions among IMF member countries. There has been a shift away from intermediate regimes according to the IMF's official exchange rate regime classification system based on de facto exchange rate policies. The de facto exchange rate classification system has helped to clarify the nature and role of members' exchange rate regimes. It has facilitated discussions with country authorities about the implementation of exchange rate regimes and hence has contributed to more effective surveillance of the international monetary system. The use of exchange controls appears to have been little influenced by the degree of flexibility of exchange rate regimes or the occurrences of currency crises.